Stability and Convergence Studies on a Numerical Model of the Arctic Ocean. - Willems,Robert Cecil (1972)
Complete solutions to the equations of motion are possible using numerical schemes. The model developed by Galt (1972) was investigated for stability and convergence. A series of runs indicated that the scheme, the three level Adams-Bashforth method for the new value of vorticity and then the successive over-relaxation method for the stream function, was stable for transport not exceeding 100 Sverdrups and a time step of one-half pendulum day. Convergence was determined by comparisons, with known analytic solutions, of phase velocity of Rossby waves, and for the steady state conditions, patterns of the stream function and the vorticity. Improved accuracy of the model was attained by using a finer grid. (Author)